FACTORS RELATED TO STUNTING IN PRESCHOOL CHILDREN IN KINDERGARTEN, BUBON DISTRICT, WEST ACEH REGENCY - Zakiyah Zakiyah; Anita Tiara; Fika Lestari; Rika Andriani (Institute of Computer Science (IOCS), 2022)
Stunting is a chronic nutritional deficiency caused by inadequate nutritional intake in the long term, and will affect the child's height. Children who experience stunting from an early age experience mental, psychomotor and intelligence disorders. The purpose of this study was to determine the factors associated with stunting in preschool children in Kindergarten, Bubon District, West Aceh Regency. The design of this research uses analytical survey design, with a cross sectional approach. The population in this study were mothers who had pre-school age children totaling 57 people using total sampling. The research was conducted in August 2020 in Kindergarten in Bubon District, West Aceh Regency, namely Permata Hati Kindergarten, State 3 Bubon Kindergarten and Bungong Melati Kindergarten. Data were collected using a questionnaire. Methods Data analysis is univariate using frequency distribution and bivariate with Chi-Square test. The results of the chi square test showed that gender (0.003), home environment (0.000), family economy (0.038), breastfeeding (0.008), birth weight (0.000) were associated with stunting in preschool children. Respondents can provide food intake in sufficient quantity, quality and maintain children's health so that they can achieve cath-up growth.